Revisiting Bungur (Lagerstroemia speciosa) from Indonesia as an Antidiabetic Agent, Its Mode of Action, and Phylogenetic Position - Nurcahyanti, Agustina Dwi Retno; Arieselia, Zita; Kurniawan, Sandy Vitria; Sofyan, Fitmawati; Wink, Michael (Pharmacognosy Reviews)
Worldwide, the diabetes epidemic is rapidly increasing and has become a growing health threat over the past few decades. The continuous investigation into the development of antidiabetic agents and treatments is crucial because current synthetic antidiabetic drugs cause adverse side effect and are often ineffective. Indonesia is blessed with a mega‑biodiversity of medicinal plants. Having an abundance of medicinal plant species has caused several problems, like the adulteration of medicinal plants when used as herbal products, and serious overharvesting resulting in the disappearance of the plants from nature. The DNA barcoding technique is a promising tool to authenticate the identity and phylogenetic position of a medicinal plant. Using DNA barcoding, a close genetic relationship of Bungur from Riau, Sumatra to related taxa from other areas is confirmed; it represents Lagerstroemia speciosa (Lythraceae). Moreover, the active secondary metabolites of Bungur are summarized and most importantly, the mechanism of action as an antidiabetic agent is described. Some of them are well‑known principles, and some are known as new mechanisms with the potential to be revisited. This report indicates that L. speciosa may have anti‑diabetic properties that might be useful in therapy of diabetes. More research is needed to determine possible side effects, and to identify its relevant chemical components.
Keywords: Antidiabetic; Bungur; Lagerstroemia speciosa; Lythraceae; Riau